Time decay in the performance benefits from repeated-sprint training in hypoxia in world-class short-track speed skaters - Deguire, S.; Billaut, F.; Bieuzen, F. (International Journal of Sports Physiology and Performance, 2023)
Purpose: In short-track speed skating, athletes need to possess specific physiological capabilities to perform explosive starts and to finish races with faster lap times than their opponents. Repeated-sprint training in hypoxia (RSH) can enhance repeated-sprint ability and high-intensity performance. This study aimed to evaluate the relationship between on- and off-ice performance indicators for training and testing purposes and how these are optimized with RSH in world-class short-track speed skaters including world and Olympic champions.